Test the Capability of the Down Flow-Up Flow Combination Filter Rate Lead (PB), Iron (FE) and Manganese (MN) which are Contained on Water Well Drill Public Residential Still Village Ndokum Siroga I Subdistrict Intersection Four Regency Karo - Sembiring, Haesti; Br Karo, Marina (International Journal of Membrane Science and Technology, 2023)
Water well drill-built government in location relocation refugees Mountain Sinabung without pre-processing and drilling depth as well vary. This affects water quality drilled wells are different at each location relocation And located in above standard water clean Which set government. This type of research is a quasi-experimental, pre-test and post-test design the object of research is water from a drilled well which is channeled to one of the people’s houses. Inspection decline rate metal Lead (Pb), Iron (Fe) And Manganese (M N) done on day the 3rd, 6th, 11th And 15th. Influence ever time contact with decline levels of Lead (Pb), Iron (Fe) and Manganese (Mn) were tested statistically by testing correlation and regression linear. The results showed that the longer the processing time the lower rate metal Lead (Pb), Iron (Fe) And Manganese (M N). Efficiency decline rate metal Lead (Pb) after processing is 32.7 %, Iron (Fe) 96% And Manganese (M N) as big 98%. Influence long processing significant to decline rate metal Lead (Pb) with a value of p = 0.033 with a value of r = -0.907, while for the reduction of metal content Iron (Fe) in a manner statistics No significant Where mark p.s = 0.05 And mark r = -0.878 so also the decrease in manganese (Mn) content was not significant where the value of p = 0.066 and mark r = -0.727. Filter Combination Down Flow-Up Flow can used for lower rate metal Lead (Pb), Iron (Fe) And Manganese (M N) water well drill.